Walk-In Users and Their Access to Online Resources in Canadian Academic Libraries - Carson, Pamela; Alexander, Krista Louise (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2020)
In the past, a member of the public could access an academic library’s collection simply by visiting the library in person and browsing the shelves. However, now that online resources are prevalent and represent the majority of collections budgets and current collections, public access has become more complicated. In Canadian academic libraries, licences negotiated for online resources generally allow on-site access for walk-in users; however access is not granted uniformly across libraries. The goal of this study was to understand whether members of the public are indeed able to access online resources in major Canadian university libraries, whether access to supporting tools was offered, how access is provided, and whether access is monitored or promoted. The study used an online survey that targeted librarians responsible for user services at Canadian Association of Research Libraries (CARL) member libraries. The survey results indicated that some level of free access to digital resources was provided to walk-in users at 90% of libraries for which a survey response was received. However, limitations in methods and modes of access and availability of supporting resources, such as software and printing, varied between the institutions. The study also found that most libraries did not actively promote or monitor non-affiliated user access.